2005
DOI: 10.1182/blood-2005-04-1565
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multiple biomarkers shows that lymphoma-associated macrophage (LAM) content is an independent predictor of survival in follicular lymphoma (FL)

Abstract: We studied the role of multiple biomarkers in determining outcome in follicular lymphoma (FL), concentrating in particular on the role of benign macrophages. The study group consisted of uniformly staged and treated patients with FL enrolled in a phase 2 trial between 1987 and 1993. All patients were younger than 61 years of age, had advanced-stage FL, and were treated with a multiagent chemotherapy regimen, BP-VACOP (bleomycin, cisplatin, etoposide, doxorubicin, cyclophosphamide, vincristine, and pred-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
328
4
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 419 publications
(353 citation statements)
references
References 40 publications
14
328
4
7
Order By: Relevance
“…21 Farinha et al 22 suggested that a high number of tumor-associated macrophages (Z15 CD68 þ macrophages/HPF) were correlated with a poor prognosis (5.0 years) in 12 of the 99 follicular lymphoma cases as opposed to 87 cases with o15 CD68 þ macrophages/HPF (16.3 years). In this respect, we found more than five macrophages/ HPF in 5% of our cases and this was also correlated with poorer overall survival compared with the group with r5 macrophages/HPF (7.6 vs 14 years, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…21 Farinha et al 22 suggested that a high number of tumor-associated macrophages (Z15 CD68 þ macrophages/HPF) were correlated with a poor prognosis (5.0 years) in 12 of the 99 follicular lymphoma cases as opposed to 87 cases with o15 CD68 þ macrophages/HPF (16.3 years). In this respect, we found more than five macrophages/ HPF in 5% of our cases and this was also correlated with poorer overall survival compared with the group with r5 macrophages/HPF (7.6 vs 14 years, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Finally, a high number of CD68 pos TAM predicts an unfavorable outcome in FL patients. 7,30 These observations raise the hypothesis that monocyte-derived IL-15 and T-cell-derived CD40L could cooperate to promote malignant B-cell growth in FL.…”
Section: Il-15 Stimulates Primary Fl B-cell Growth In the Presence Ofmentioning
confidence: 85%
“…6 Finally, microarray gene expression studies, quantitative-PCR analyses and immunohistochemical experiments suggest that a high numbers of CD68 pos or CD163 pos tumor-associated macrophages (TAM) is of bad prognosis in FL patients treated with chemotherapy not associated with antibody-based immunotherapy. [7][8][9][10][11] Moreover, in diffuse large B-cell lymphomas, the most frequent aggressive GC-derived lymphoma, monocytes deliver survival signals to malignant B cells at least in part through the production of B-cell activating factor (BAFF). 12 Nevertheless, how TAM favor FL B-cell growth in situ and what could be the cooperative role of neighboring T cells in this context have not been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cell lineage markers employed in this study do not permit further delineation of the identity of the non-B/non-T cell population, it is likely that these cells encompass, at least in part, monocyte/macrophage lineage cells. The frequency of CD68þ macrophages in follicular lymphoma has been previously correlated with poorer overall survival (19). In that study, 12 of 99 cases demonstrated more than 15 CD68þ macrophages per high power field.…”
mentioning
confidence: 79%